(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2021)
Introduction: Amniocentesis is a procedure in which amniotic fluid is collected from the amniotic cavity for testing or treatment. Amniotic fluid is the fluid that surrounds and protects a baby during pregnancy. Amniotic fluid contains fetal cells and various proteins and provides valuable information about baby’s health. Aim: To evaluate the risk and associated complications during diagnostic amniocentesis. Methods: This prospective study was conducted by performing amniocentesis among pregnant ladies of early second trimester at Dhaka CMH, and Aklima General Hospital Limited, Mirpur, Dhaka from July 2016 to June 2019. A total of 50 patients were selected by age of the patient, history of previous pregnancy outcome, parental haemoglobinopathy and few other factors triggered these cases to be put under this study. Results: No major complications have been observed during and after the procedure because of appropriate pre-operative and post-operative management. Conclusion: There are some common and known risks which are associated with amniocentesis like miscarriage, amnionitis, fetal trauma etc. Through skilled execution with the help of real-time ultrasound guidance and proper pre-operative and post-operative care, we can avoid complications and get benefit from amniocentesis. JAFMC Bangladesh. Vol 15, No 1 (June) 2020: 42-45